Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1248/bpb.28.1394
|View full text |Cite
|
Sign up to set email alerts
|

The 3-Hydroxy-3-methylglutaryl Coenzyme A (HMG-CoA) Reductase Inhibitor, Lovastatin (Statin) Ameliorates CCK-Induced Acute Pancreatitis in Rats

Abstract: Acute pancreatitis (AP) is a clinical entity that is believed to have intracellular activation of digestive enzymes and autodigestion of the pancreas as its central pathophysiologic cause. The noninfectious destruction of pancreatic parenchyma quickly induces an inflammatory reaction at the site of injury. Histologically, AP is characterized by interstitial edema, vacuolization, inflammation and acinar cell necrosis. The diagnosis of AP is based on pancreatic edema index (pancreas weight/body weight) and pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…There is a therapeutic window between onset of symptoms and the development of distant organ damage in acute pancreatitis, allowing the employment of therapeutic and preventive options that might alter the natural history of the disease [41]. There was a dose-dependent effect of taurine in the treatment of acute pancreatitis, and the taurine pretreatment time point is from 10 min to 24 h to reduce experimental liver injury [15,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…There is a therapeutic window between onset of symptoms and the development of distant organ damage in acute pancreatitis, allowing the employment of therapeutic and preventive options that might alter the natural history of the disease [41]. There was a dose-dependent effect of taurine in the treatment of acute pancreatitis, and the taurine pretreatment time point is from 10 min to 24 h to reduce experimental liver injury [15,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above theoretical benefits, Choi et al [33] have demonstrated an increase in Heat Shock Protein (HSP) 60 (HSPs are responsible for maintaining cellular homeostasis and help cells survive stress conditions by repairing damaged proteins)and decrease in the release of inflammatory mediators (e.g., IL-1beta, TNF-alpha and IL-6) when statins were used in rats with cholecystokininoctapeptide (CCK)-induced pancreatitis. Subsequent animal studies have also demonstrated benefit of statin therapy in acute via reduction of IL-10 levels and myeloperoxidase activity [28] .…”
Section: Discussionmentioning
confidence: 99%
“…18,23 In animal models, statins have decreased the inflammatory mediators released during AP (interleukin [IL] 1A, IL-6, and tumor necrosis factor >). 24 The antagonist of IL-1 or anti-TNF has reduced severity and improved survival in AP in animal studies. 25 Our study indicated that long-term statin therapy did not modify or improve the outcome of AP measured by some clinical parameters (decreased need of emergency surgery, hospital stay, intensive care treatment, or mortality).…”
Section: Discussionmentioning
confidence: 99%